PENGARUH INTEGRITAS, INDEPENDENSI, OBYEKTIVITAS DAN KOMPETENSI TERHADAP KINERJA APIP MELALUI KUALITAS AUDIT DI INSPEKTORAT DAERAH KABUPATEN BARITO SELATAN - Desso Robertio robert (KINDAI, 2023)
ABSTRACT The purpose of this study was to determine and analyze the effect of integrity, independence, objectivity and competence on APIP performance through audit quality. This type of research uses a quantitative descriptive method. The independent variables consist of integrity, independence, objectivity and competence, the dependent variable is APIP performance and the intervening variable is audit quality. The sample used in this study was 29 people from 41 population, namely employees who carry out direct supervisory duties (Auditors and PPUPD). The sampling technique uses the Slovin formula. Data collection was carried out by distributing questionnaires, direct observation and interviews. Data analysis technique uses descriptive analysis and path analysis (Path Analysis) with the help of Smart PLS version 3.3.2 Professional. The results of the study show that the direct effect: (1) integrity has a significant effect on audit quality; (2) independence has a significant effect on audit quality; (3) objectivity has a significant effect on audit quality; (4) competence has no significant effect on audit quality; (5) integrity has a significant effect on APIP performance; (6) independence has no significant effect on APIP performance; (7) objectivity has a significant effect on APIP performance; (8) competence has a significant effect on APIP performance; (9) audit quality has a significant effect on APIP performance. As for the indirect effect: (10) integrity has a significant effect on APIP performance through audit quality; (11) independence has a significant effect on APIP performance through audit quality; (12) competence has a significant effect on APIP performance through audit quality; (13) competence has no significant effect on APIP performance through audit quality at the Inspektorat Daerah Kabupaten Barito Selatan Keywords: integrity, independence, objectivity, audit quality and APIP performance.